Approaching the precursor nuclei of the third r-process peak with RIBs. Issue 1 (January 2016) - Domingo-Pardo, C; Caballero-Folch, R; Agramunt, J; Algora, A; Arcones, A; Ameil, F; Ayyad, Y; Benlliure, J; Bowry, M; Calviño, F; Cano-Ott, D; Cortés, G; et al.
Abstract: The rapid neutron nucleosynthesis process involves an enormous amount of very exotic neutron-rich nuclei, which represent a theoretical and experimental challenge. Two of the main decay properties that affect the final abundance distribution the most are half-lives and neutron branching ratios. Using fragmentation of a primary 238 U beam at GSI we were able to measure such properties for several neutron-rich nuclei from 208 Hg to 218 Pb. This contribution provides a short update on the status of the data analysis of this experiment, together with a compilation of the latest results published in this mass region, both experimental and theoretical. The impact of the uncertainties connected with the beta-decay rates and with beta-delayed neutron emission is illustrated on the basis of r -process network calculations. In order to obtain a reasonable reproduction of the third r -process peak, it is expected that both half-lives and neutron branching ratios are substantially smaller, than those based on FRDM+QRPA, commonly used in r-process model calculations. Further measurements around N ∼ 126 are required for a reliable modelling of the underlying nuclear structure, and for performing more realistic r-process abundance calculations.